Weight growth velocity and growth outcomes in very-low-birth-weight infants developing major morbidities - Ting-Hsuan Sung; Chi-Shuo Lin; Mei-Jy Jeng; Pei-Chen Tsao; Wei-Yu Chen; Yu-Sheng Lee (Pediatrics and Neonatology)
Background: Extrauterine growth restriction (EUGR) is common in very-low-birth-weight-infants and may be associated with poor neurodevelopment. The growth velocity of preterm infants is increasing over decades, but the relationship between growth velocity, EUGR, and morbidities of preterm infants remains unknown. Methods: A total of 263 infants born between 2012 and 2020, with birthweight <1500 g and gestational age of 24–33 weeks, were included. Birthweight and weight on day of evaluation point (corrected gestational age 36 weeks or discharged, whenever comes first) were converted to age-specific and gender-specific Z-scores and analyzed by multivariable modeling. The average growth velocity was calculated by the exponential model. Results: Average growth velocity from birth to the evaluation point was 11.8 ± 0.3 g/kg/day. The maximum growth velocity from birth to week 8 postnatal occurred at week 4 postnatal (16.4 ± 0.9 g/kg/day). Infants with smaller birth weight, higher gestational age, and indication of intestinal surgery or those who need more days to achieve full enteral feeding were more favorable to have a weight lower than the 10th centile at the evaluation point. By contrast, most comorbidities of prematurity did not affect either lower age-specific weight Z-scores on the evaluation point or larger change in weight Z-score between birth and evaluation point. Conclusion: EUGR was associated with gestational age and birth weight. Infants with moderate-to-severe bronchopulmonary dysplasia, high-grade intraventricular hemorrhage, or retinopathy of prematurity tend to have slower growth velocity at 3–5 weeks postnatal, but these did not contribute to EUGR.